Public investments´ ex-post evaluation: the case of Portuguese Northern Region - Emília Malcata Rebelo (2010)
The paper presents a methodology for an aggregate ex-post economic evaluation of the regional impact of a given set of large investment projects. This methodology seeks to address the following goals: (1) analysis and quantification of regional benefits accrued from public investments already implemented, (2) support the transparent and efficient use of public money, and (3) guarantee a fair spatial distribution of resources/investments within a certain region. In order to achieve these goals, the paper presents a conceptual model tested in the Northern Region of Portugal. It consists in the measurement of the ex-post costs and benefits of investments already performed in public works and infrastructures, and in the respective comparison with ex-ante goals, in order to define an efficiency measure. This measure allows for subsequent inter and intra-regional comparisons in order to support the design of responsive local and regional planning policies. Adopting an integrative planning standpoint, comparisons are made among this methodology and similar evaluation methodologies developed elsewhere. This paper is expected to contribute to the most important goal of the European regional policy: cohesion at the social, economic and territorial levels.